A construction strategy of ferroelectrics by the molten salt method and its application in the energy field. Issue 26 (22nd June 2020) - Fu, Jing; Hou, Yudong; Liu, Xuepeng; Zheng, Mupeng; Zhu, Mankang
Abstract : The critical issues and the recent progress of molten salt preparation of ferroelectrics and their application in the energy field. Abstract : Ferroelectrics are a class of functional materials that have spontaneous polarization and whose direction can be modulated by external electric fields. The improvement of the electrical properties of ferroelectrics is closely related to the control of their crystal structure and morphology. The molten salt method is a chemical synthesis method in which a molten salt functions as a high-temperature liquid solvent. The special molten salt reaction environment is conducive to the dissolution of raw materials, the transport of reactants, and the directional assembly of basic units to prepare scale- and shape-controllable target materials. In particular, ferroelectrics synthesized by the molten salt method have a variety of technical advantages, such as controllable morphology (0D, 1D and 2D), high dielectric constant, high piezoelectric performance, and strong sintering activity. Therefore, ferroelectrics synthesized by this process have been used in important applications in the energy field in different forms, such as single crystals, textured ceramics, piezoelectric composites, oriented composites, multilayer composites and ferroelectric ceramics. This review article highlights the critical issues and the recent progress of molten salt preparation of ferroelectrics and their application from the viewpoint of synthesis strategies, reaction mechanisms, and energy device assembly. It is anticipated that this review can serve as an overview and evaluation of the state-of-the-art molten salt synthesis of ferroelectrics and their design for applications in energy conversion and energy storage devices.